PENINGKATAN KOMPETENSI KEWIRAUSAHAAN BERBASIS INOVASI MASYARAKAT BATANG KAPAS, KABUPATEN PESISIR SELATAN - Suhanda, Mya Yuwanita; Astari, Silvy; Nanda, Nanda; Adha, Howardi Visza (Komunitas Manajemen Kompetitif, 2024)
Community service is organized by lecturers at the Faculty of Business and Economics, Baiturrahmah University. The purpose of this activity is to improve innovation-based entrepreneurial competency for Small and Medium Enterprises (SMEs) owners in Nagari Koto Nan Duo, Batang Kapas District, Pesisir Selatan Regency, on August 10, 2024, West Sumatra Province. The author seeks to support this program by delivering material on entrepreneurship, innovation and creativity. By delivering this material to SME owners, the author hopes that SME actors can apply the concept of innovation in the businesses they are currently running. The success of this activity will be seen from the participants' understanding of the concept of innovation in entrepreneurship. The author hopes that similar activities can be held in various regions so that more SME owners gain knowledge about this innovation-based entrepreneurship. Keywords: